(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article considers the main problems and prospects for the investment development of the tourism industry in the Bukhara region. The main trends in the development of investment activities in the field of tourism in Uzbekistan are also described. As well as the tourism potential of the cities of the republic and the use of investments.